Evaluation of the SIBISA Application System in Population Administration Services at the Medan City Disdukcapil - Heryanto Richard Sihombing; Badaruddin Badaruddin; Bengkel Ginting (PERSPEKTIF, 2025)
This study aims to evaluate the performance of the Population Data-Based Information System (SIBISA) in population administration services at the Population and Civil Registration Office (Disdukcapil) of Medan City, using the DeLone and McLean models. The research was conducted using a qualitative descriptive approach, incorporating interviews, observation, and documentation techniques. The results of the evaluation show that, although the SIBISA application provides easy access and transparency of services, several obstacles remain, including limited infrastructure, low digital literacy among the community, and suboptimal data integration between agencies. Additionally, variations in service quality and inadequate officer training also impact user satisfaction levels. This research emphasizes the importance of technical capacity building, digital inclusion strategies, and cross-sector system consolidation to realize inclusive, effective, and sustainable digital-based public services.